2017
DOI: 10.2337/dc17-0594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Behavioral Intervention Strategy for Adoption and Maintenance of a Physically Active Lifestyle: The Italian Diabetes and Exercise Study 2 (IDES_2)

Abstract: OBJECTIVEAdherence to physical activity (PA) recommendations is hampered by the lack of effective strategies to promote behavior change. The Italian Diabetes and Exercise Study 2 (IDES_2) is a randomized controlled trial evaluating a novel behavioral intervention strategy for increasing PA and decreasing sedentary time (SED-time) in patients with type 2 diabetes. RESEARCH DESIGN AND METHODSThe study randomized 300 physically inactive and sedentary patients with type 2 diabetes 1:1 to receive theoretical and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
23
0
4
Order By: Relevance
“…The weighted percentage of participants with hypertension was much higher in the diabetic than in the nondiabetic subpopulation (68.18% and 36.03%, respectively) and shows the high rate of co-occurrence of these two diseases. People with diabetes are also more likely to be physically inactive [10], and behavioral intervention strategies have been implemented to help people with diabetes maintain a physically active lifestyle [11]. Similarly, our analysis showed that diabetic participants were 14.86% less likely to be physically active.…”
Section: Discussionmentioning
confidence: 52%
“…The weighted percentage of participants with hypertension was much higher in the diabetic than in the nondiabetic subpopulation (68.18% and 36.03%, respectively) and shows the high rate of co-occurrence of these two diseases. People with diabetes are also more likely to be physically inactive [10], and behavioral intervention strategies have been implemented to help people with diabetes maintain a physically active lifestyle [11]. Similarly, our analysis showed that diabetic participants were 14.86% less likely to be physically active.…”
Section: Discussionmentioning
confidence: 52%
“…In our study, women demonstrated a lower inclination for physical exercise. However, this finding may be affected by social context and educational level [39,44] of the Italian population and further investigations are necessary to highlight the detailed reasons underlying this trend. Overall, the results show a population needing a stronger motivation to maintain good adherence to correct lifestyles while getting older, maybe due to the increased fragility.…”
Section: Discussionmentioning
confidence: 96%
“…51 Typically, the studies recruited participants from the general population (k=26) or a population with a chronic disease risk factor (k=17) (generally overweight and/or obesity, occasionally in conjunction with another risk factor). Clinical conditions 36 47 Balducci et al 72 Table 1 Continued activity sessions (k=2). By contrast, non-workplace interventions almost always used some form of counselling/education (k=29), commonly used device self-monitoring (k=18) and occasionally used environmental modification (k=8), prompting (k=6), structured activity (k=4) and financial incentives (k=1).…”
Section: Systematic Reviewmentioning
confidence: 99%